WDR45 Mutation Impairs the Autophagic Degradation of Transferrin Receptor and Promotes Ferroptosis - Xiong, Qiuhong; Li, Xin; Li, Wenjing; Chen, Guangxin; Xiao, Han; Li, Ping; Wu, Changxin (Frontiers in Molecular Biosciences, 2021)
WDR45 is an autophagy-related protein that involves in the formation of autophagosome. Mutations in WDR45 lead to the impairment of autophagy which is associated with the human β-propeller protein-associated neurodegeneration (BPAN). However, the relationship between autophagy and brain iron accumulation in patients with BPAN remains unclear. Here, we demonstrated that transferrin receptor (TfRC) which is critical for the iron import of cells was degraded via autophagy. TfRC was accumulated after the inhibition of autophagy by treatment with autophagic inhibitor chloroquine or knockdown of ATG2A. The intracellular iron content was increased in cells overexpressing TfRC or mutant WDR45, however, ferritin H (FTH) chain was decreased. Increased TfRC and simultaneously decreased FTH consequently resulted in an elevated level of ferrous iron (Fe2+) which further promoted cell ferroptosis, demonstrated by the increased lipid peroxidation and reactive oxygen species (ROS) and the decreased glutathione peroxidase 4 (GPX4) and cell viability. Taken together, these findings provide a piece of important evidence that WDR45 deficiency impairs autophagic degradation of TfRC, therefore leading to iron accumulation, and the elevated iron promotes ferroptosis which may contribute to the progression of BPAN.